Epidemiological aspects of adherence to the treatment of hypertension - Andrade,Jadelson P. (2002)
OBJECTIVE: To analyze the reasons given by patients for interrupting their pharmacological treatment of hypertension. METHODS: We carried out an observational cross-sectional study, in which a questionnaire was applied and blood pressure was measured in 401 patients in different centers of the state of Bahia. The patients selected had been diagnosed with hypertension and were not on antihypertensive treatment for at least 60 days. Clinical and epidemiological characteristics of the groups were analyzed. RESULTS: Of the 401 patients, 58.4% were females, 55.6% of whom white; 60.5% of the males were white. The major reasons alleged for not adhering to treatment were as follows (for males and females respectively): normalization of blood pressure (41.3% and 42.3%); side effects of the medications (31.7% and 24.8%); forgetting to use the medication (25.2% and 20.1%); cost of medication (21.6% and 20.1%); fear of mixing alcohol and medication (23.4% and 3.8%); ignoring the need for continuing the treatment (15% and 21.8%); use of an alternative treatment (11.4% and 17.1%); fear of intoxication (9.6% and 12.4%); fear of hypotension (9.6% and 12%); and fear of mixing the medication with other drugs (8.4% and 6.1%). CONCLUSION: Our data suggest that most factors concerning the abandonment of the treatment of hypertension are related to lack of information, and that, despite the advancement in antihypertensive drugs, side effects still account for most abandonments of treatment.